Efficacy of Caprini risk assessment model in predicting venous thromboembolism risks among Asian surgical patients - Liew, Ngoh Chin; Lee, Limi; Ahmad Zaidi, Ahmad Al-Hafeez; Teoh, Yan Jun (Malaysian Medical Association, 2024)
Introduction: Caprini risk assessment model (RAM) has been validated in Caucasians but evidence of its suitability in Asian surgical patients is still unknown. This study aims to determine the efficacy of Caprini model in venous thromboembolism (VTE) risk assessment among Asian surgical patients. Materials and Methods: Consecutive surgical patients with Asian ethnicities admitted to a tertiary public hospital between January 2013 and December 2014, were included. Their demographic details, VTE risk factors and scores based on Caprini RAM were recorded. Primary outcome of this study was symptomatic VTE within 90 days of hospitalisation. Fisher’s exact test and Lasso regression were performed for statistical analysis. Results: A total of 4206 patients were included in this study. Distribution of this study population by risk level was very low, 14.7%; low, 44.1%; moderate, 25.6% and high, 15.7%. The overall symptomatic VTE incidence within 90 days was 0.5%. The incidence of deep venous thrombosis (DVT), pulmonary embolism (PE) and both was 0.31%, 0.19% and 0.05% respectively. VTE incidence by risk category was very low, 0%; low, 0.16%; moderate, 0.37% and high, 2.12%. Obesity (BMI >25), history of prior major surgery, history of DVT/PE and high-risk category (scores ≥5) were significant VTE factors with odds ratio > 5.0. Following the Caprini RAM with ACCP preventive recommendations, an estimated 85% of surgical patients would need prophylaxis. Conclusion: The overall VTE incidence among Asian surgical patients is low. Prophylaxis using Caprini RAM may subject a low incidence patient population to over utilisation of thromboprophylaxis and therefore not cost-effective when applied to Asian patients.